On the Influence of Shevchenko's Autobiography on Kulish's - Rosovetkskyi , Stanislav (Current issues of Ukrainian linguistics: theory and practice, 2025)
In honor of the 200th anniversary of P. Kulish's birth, the article offers a multi-level comparison of autobiographies of two prominent Ukrainian writers of the 19th century. In the categories and concepts of modern literary criticism, the hypothesis of literary influence of T. Shevchenko on P. Kulish's perception of artistic autobiography genre is checked and confirmed. For this purpose, three texts are compared: an autograph of "Autobiography" by T. Shevchenko, deeply edited by P. Kulish for printing in "People's Reading" journal, a version of T. Shevchenko's "Autobiography" and an autobiography "My Life" by P. Kulish. The comparison is carried out at narratological, compositional, genre and intertextual levels. The historical background of the creation of each of the texts is analyzed. It is proved that the autograph of T. Shevchenko's "Autobiography" and P. Kulish's "My Life" both belong to the genre of artistic autobiography and have a compressed narrative structure. It is confirmed that T. Shevchenko didn't have extra-literary reasons for creating a third-person autobiography, unlike P. Kulish, who, moreover, was very likely to come under the literary influence of the text of T. Shevchenko and developed T. Shevchenko's narrative structure in his artistic autobiography. At the same time, it is assumed that literary influence might not be the main argument in choosing a third-person narration, since there were extra-literary reasons for keeping P. Kulish's incognito. It is noted that the text "My Life" of P. Kulish is more functional in the aspects of orientation to objectivity, emotional pressure and moderation of the author's image in literary life. Its narrative structure is compressed precisely for the sake of objectivity, addressees and consignees are implicit and difficult to isolate on each of the layers of the narrative structure precisely to mimic the non-fiction. The text of a letter to the author integrated into "My Life" is the only exception. It is concluded that hypothesis about literary influence of T. Shevchenko on P. Kulish within the genre of artistic autobiography is reliable and well-reasoned. To the author's mind, further studies should focus on finding evidence of unconscious literary influence of T. Shevchenko on P. Kulish in other genres, chances of discovering which in future are rather high.
Keywords: narration, influence, autobiography, textology, Taras Shevchenko, Panteleimon Kulish